Family listening/circle program: The experience of community action projects to promote family and community wellness in three tribal communities in New Mexico - Rae, Rebecca; Belone, Lorenda; Tafoya, Eleanor; Yepa, Melissa; Cohoe-Belone, Benalda; Burbank, Ira; Orosco, Ardena; Lacroix-Garcia, Pius; Sherpa, Mingma; Wallerstein, Nina (Frontiers in Public Health, 2023)
The Family Listening/Circle Program (FLCP) is a community-based participatory research (CBPR), culture-centered, intergenerational family strengthening program that was co-developed in partnership with the University of New Mexico’s Center for Participatory Research (UNM-CPR) and three tribal communities in New Mexico. The tribal research teams (TRTs) from each community worked with UNM-CPR to co-create, pilot, implement, and evaluate the tribally-specific FL/CP curricula centered in their own tribal histories, language, knowledge, visions and actions for the future. The Family Listening/Circle Program brings together fourth and fifth graders, their parents, care givers, and elders to reduce risky behaviors associated with initiation of substance use among the youth, and to strengthen family communication and connectedness to culture and language as protective factors. A key component of the FL/CP involves the planning and completion of community action projects (CAPs) by participating families. The CAPs provide an empowerment and community benefit focus based on Paulo Freire’s philosophy that people can become agents of change if they identify and work on issues that are important to them. The community action projects are also centered in Indigenous values and practices of reciprocity, responsibility and being active members of the community. This article provides historical background on the CBPR partnership that created the tribally specific Family Listening/Circle Program and shares each communities' experience in the planning and completion of their CAPs including challenges, community benefits, and outcomes.